Factors determining the prognosis of people with type 1 diabetes – current perspective - Araszkiewicz, Aleksandra; Trzaska, Kacper; Soukharev, Anna; Spławski, Jakub; Wolbach, Jan; Marek, Piotr; Dubel, Kinga; Wojak, Weronika; Zozulińska-Ziółkiewicz, Dorota (Journal of Medical Science, 2025)
A multitude of factors strongly influences the prognosis of subjects with type 1 diabetes. In the literature, it’s notable that only a limited number of studies simultaneously address multiple factors. Our objective is to identify and compile current papers that thoroughly examine these factors, offering a comprehensive overview of the various elements that can influence both life expectancy and the prevalence of complications among individuals with type 1 diabetes. In the overview, we included modifiable and non-modifiable factors. The paper covers technology development, comorbidities as well as acute and chronic complications as predictors. Greater focus on the significance of sex and age as a risk of macrovascular diabetes-related complications, age at onset of diabetes, and episodes of acute complications, can lead to more targeted management of type 1 diabetes and therefore, higher life expectancy. The article also discusses such environmental factors as lifestyle, education, and access to the healthcare system affecting better handling of type 1 diabetes. This overview emphasizes the plurality of factors that are considered in type 1 diabetes, which might be crucial to prolonging life expectancy and reducing the prevalence of complications.